Cultures of Empire: Rethinking Venetian Rule 1400–1700
1 online resource.
Keywords: This book investigates perceptions, modes, and techniques of Venetian rule in the early modern Eastern Mediterranean (1400–1700). Against the backdrop of the controversial notion of the Venetian realm as a colonial empire, essays from a range of specialists examine how Venice negotiated control over the territories, resources, and traditions of different empires (Byzantine, Roman, Mamluk, Ottoman) while developing its own claims of authority. Focusing in particular on questions of belonging and status in the Venetian overseas territories, the volume incorporates observations on the daily realities of Venetian rule: how did Venice negotiate claims of authority in light of former and ongoing imperial belongings? What was the status of colonial subjects and ships in the metropolis and in foreign territories? In what ways did Venice accept and continue old forms of imperial belonging? Did subordinate entities join in a shared communal identity? The volume opens new perspectives on Venetian rule at the crossroads of empire and early modern statehood: a polity negotiating and entangling empire. Contributors are Housni Alkhateeb Shehada, Giacomo Corazzol, Nicholas Davidson, Renard Gluzman, Deborah Howard, David Jacoby (ZL), Marianna Kolyvà, Franz-Julius Morche, Reinhold C. Mueller, Monique O’Connell, Gerassimos D. Pagratis, Tassos Papacostas, Maria Pia Pedani (†), Dorit Raines, and E. Natalie Rothman.